Theoretical and methodological framework for the development of tourist enterprises on industrial territory - Balashova, Raisa (Skhid, 2013)
Certainly characteristic and specific features of activity of tourist enterprises on industrial territory, investigational processes them current activity and economic development, methodology of exposure and generalization of priority factors of development and their connection is offered with industrial territory.